Growth Curve and Antibacterial Activity Test of Endophytic Bacteria Isolates 1 (IBE1) from Labu Koteka (Lagenaria siceraria) Against Escherochoa coli, Pseudomonas aeruginosa and MRSA - Putri, Silvy Rizka; Djamaan, Akmal; Agustien, Anthoni (Jurnal Biologi Tropis, 2025)
The rising incidence of antibiotic-resistant bacteria presents a considerable global health threat, requiring the immediate creation of new antimicrobial drugs. A possible strategy involves investigating antibiotics sourced from endophytic bacteria, which are microorganisms that inhabit plant tissues symbiotically. This research is to assess the inhibitory efficacy of endophytic bacteria derived from Lagenaria sicerari against, Escherichia coli, Pseudomonas aeruginosa, and methicillin-resistant Staphylococcus aureus (MRSA). The identified endophytic bacteria were cultivated in a fermentation medium to synthesize antibiotics, and their growth curves were examined. Subsequently, antibacterial activity assays were performed against the three harmful bacteria, measuring the sizes of the clear inhibitory zones. The results indicated that Isolated Bacteria Endophytic (IBE) 1 attained optimal inoculum levels at 24 hours and sustained the stationary phase from 24 to 36 hours. The isolates exhibited optimum fermentation on a medium utilizing glucose as the carbon source, with a carbon-to-nitrogen ratio of 5. IBE 1 had the most effective antibacterial action against P. aeruginosa, with a moderate inhibition characterized by clear zone widths of 10.80 mm. The findings indicate that endophytic bacteria from Lagenaria siceraria may serve as promising sources of new antimicrobial drugs, especially against Pseudomonas aeruginosa.